Comparison Between OFAT and RSM Approaches for the Optimization of Endoglucanase Production by Alkaliphilic Aspergillus oryzae and Its Application in the Pulp and Paper Industry (Journal of Environmental Bioremediation and Toxicology, 2024)
The production of endoglucanase (CMCase) from Aspergillus oryzae has been studied under a submerged fermentation technique using a range of physical and nutritional factors. These include temperature, pH, incubation time, and nitrogen sources, which were studied under a one-factor-at-a-time (OFAT) approach using Cellulose Powder as the sole source of carbon. The use of OFAT produced a maximum CMCase of 3.55 U/mL at an optimum pH of 8, temperature 28 ºC, nitrogen source (1 g/L NH4SO4) and 7th day incubation time. The use of Response Surface Methodology (RSM) resulted in 3.96 U/ml at pH 8.5, a temperature of 40 ºC, an ammonium sulfate concentration of 3%, and a 7-day incubation. This results in an increase of 0.45 U/mL in enzyme production compared to OFAT. Alkaline endoglucanase from A. oryzae was also evaluated for its deinking potential. An A4 paper was printed with the word 'deinking' for approximately 640 words using a Xerox printer. After the enzymatic, chemical, and control pulping processes, as well as flotation, the resultant pulp was prepared according to TAPPI standards for testing pulp brightness, tensile strength, bursting strength, and tearing strength. The percentage brightness result following A. Oryzae enzymatic treatment indicated an improvement in ISO brightness of 2.36% and 0.48% for the control and chemical, respectively, compared to the prepared hand sheet. The tensile strength of the printed waste paper improved by 180 N/m and 253 N/m, respectively, when compared to the control and chemical deinking process. In terms of bursting strength, enzymatic deinking was increased by 11 kPa and 8 kPa, while the tearing strength showed an improvement of 3 mN and 9 mN compared to the control and chemical deinking, respectively.
Keywords: Endoglucanase; RSM; OFAT; Aspergillus oryzae; CMCase